Huruf Ba (ب) Jar dalam Bahasa Arab dan Maknanya dalam al-Quran Surah al-Baqarah - Saida Gani (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to examine the letter Ba (ب) and its meaning in surah al-Baqarah. The letter Ba (ب) is one of the ma'ani letters whose meaning may change at any time based on its grammatical structure. A type of qualitative research that is descriptive in nature that makes the source of data in the form of the letter ba (ب) in Arabic, and the secondary data is the meaning of the letter ba (ب) itself either in the form of ideas or interpretations of sentences or verses that use the letter ba (ب). The results showed that the letter ba (ب) in surah al-Baqarah means al-ilshaq among them in QS/2: 2, 4, 8, 15, 19, 25. And it means al-zaidah (al-taukid) among them in QS/2: 8, 74, 85, 96. And it means al-ta'diyah among them QS/2: 17 and 20. Meaning al-sababiyah (al-ta'lil) QS/2:22, 26, 30, 50. Meaning al-mujawazah QS/2:31 and 33. Meaning al-isti'anah QS/2:67, 73, 85, 87. Meaning al-muqabalah (al-'iwadh) QS/2:10, 16, 41, 61, 95. And it means al-musahabah QS/2:87 and 92